2013
DOI: 10.1111/1750-3841.12249
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Swiss Cheese from 5 Different Factories by High Impact Volatile Organic Compound Profiles Determined by Odor Activity Value Using Selected Ion Flow Tube Mass Spectrometry and Odor Threshold

Abstract: Swiss cheese contains more than 200 volatile organic compounds (VOCs). Gas chromatography-mass spectrometry has been utilized for the analysis of volatile compounds in food products; however, it is not sensitive enough to measure VOCs directly in the headspace of a food at low concentrations. Selected ion flow tube mass spectrometry (SIFT-MS) provides a basis for determining the concentrations of VOCs in the head space of the sample in real time at low concentration levels of parts per billion/trillion by volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 19 publications
(27 reference statements)
0
21
0
2
Order By: Relevance
“…So it is generally assumed that the odorants with higher OAVs contribute in a stronger manner to the overall aroma (Callejon et al 2008). The odor threshold has been previously reported in related literatures (Burdock 2004;Callejon et al 2008;Marchand et al 2000;Peinado et al 2004;Piccino et al 2013;Taylor et al 2013;Vilanova and Martínez 2007). Compounds in the Table 6 are ranked according to the maximum OAV reached in the eight SAV samples.…”
Section: Oav Calculation and Aroma Wheelmentioning
confidence: 86%
See 1 more Smart Citation
“…So it is generally assumed that the odorants with higher OAVs contribute in a stronger manner to the overall aroma (Callejon et al 2008). The odor threshold has been previously reported in related literatures (Burdock 2004;Callejon et al 2008;Marchand et al 2000;Peinado et al 2004;Piccino et al 2013;Taylor et al 2013;Vilanova and Martínez 2007). Compounds in the Table 6 are ranked according to the maximum OAV reached in the eight SAV samples.…”
Section: Oav Calculation and Aroma Wheelmentioning
confidence: 86%
“…Comparing aroma wheel of SAV to sensory analysis of Sherry vinegar (Callejon et al 2008), we found roasty was a unique flavor for SAV. This preliminary comparison between aroma wheel b Odor activity value defined as ratio between odor concentration and odor threshold c Each compound was attributed to 1 or more classes of the following 6 classes of sensory descriptors: (1), floral, (2), roasty, (3), nutty, (4), fatty, (5), fruity, (6), woody d Burdock (2004) e Callejon et al (2008) f Taylor et al (2013) g Marchand et al (2000) h Piccino et al (2013) i Vilanova and Martínez (2007) * The highest odor activity values of the aroma compounds among the eight Shanxi aged vinegar samples and sensory analysis demonstrated a previous viewpoint: aroma wheel could be a replacement when a sensory analysis is not available or affordable (Capone et al 2013). Among these SAV samples, TB-3-Z and S-3-D presented relatively high scores on most sensory descriptors.…”
Section: Oav Calculation and Aroma Wheelmentioning
confidence: 99%
“…Several investigations have also been used to assess various qualities of cheese. The VOC profile was used to distinguish between Italian parmesan and New Zealand parmesan [150] and, in conjunction with odor activity values, to differentiate Swiss cheese production from five different factories [151]. In another investigation the VOC profile examined using SIFT-MS aided the evaluation of parameters responsible for split defects in Swiss cheese [152].…”
Section: Food and Food Technologymentioning
confidence: 99%
“…SIM scans limit the number of masses to be counted per scan thus allowing longer detection time per mass and delivers higher precision of quantification. A method containing 29 compounds considered to be of high impact in Swiss cheese (Taylor et al, 2013) was developed using the SIM scan mode and method development software (LabSyft) of the V200™. The scan duration was 2 min 10 s. Standards were run at the start of each day and calibrated with ethylbenzene, tetrafluorobenzene, toluene, hexafluorobenzene, ethylene, octafluorotoluene, benzene and isobutene.…”
Section: Instrumental Analysismentioning
confidence: 99%
“…The key volatiles in Swiss cheese include 2e3, butanedione, 2-methylpropanal, 3-methylbutanoic acid, 3-methylindole, acetic acid, butanoic acid, ethyl butanoate, dimethyl disulfide, dimethyl sulfide, dimethyl trisulfide, ethyl hexanoate, furaneol, methional, methanol, methanethiol, propanoic acid, and tetramethylpyrazine (Smit, Smit, & Engels, 2005;Taylor, Wick, Castada, Kent, & Harper, 2013).…”
Section: Introductionmentioning
confidence: 99%